C3 inhibition with pegcetacoplan in subjects with paroxysmal nocturnal hemoglobinuria treated with eculizumab - Castro, Carlos; Grossi, Federico; Weitz, Ilene Ceil; Maciejewski, Jaroslaw; Sharma, Vivek; Roman, Eloy; Brodsky, Robert A.; Tan, Lisa; Di Casoli, Carl; El Mehdi, Delphine; Deschatelets, Pascal; Francois, Cedric (American journal of hematology, 2020)
Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired, life‐threatening hematologic disease characterized by chronic complement‐mediated hemolysis and thrombosis. Despite treatment with eculizumab, a C5 inhibitor, 72% of individuals remain anemic. Pegcetacoplan (APL‐2), a PEGylated C3 inhibitor, has the potential to provide more complete hemolysis control in patients with PNH. This open‐label, phase Ib study was designed to assess the safety, tolerability, and pharmacokinetics of pegcetacoplan in subjects with PNH who remained anemic during treatment with eculizumab. Pharmacodynamic endpoints were also assessed as an exploratory objective of this study. Data are presented for six subjects in cohort 4 who received treatment for up to 2 years. In total, 427 treatment‐emergent adverse events (TEAEs) were reported, 68 of which were possibly related to the study drug. Eight serious TEAEs occurred in two subjects; three of these events were considered possibly related to the study drug. Pegcetacoplan pharmacokinetic concentrations accumulated with repeated dosing, and steady state was reached at approximately 6‐8 weeks. Lactate dehydrogenase levels were well controlled by eculizumab at baseline. Pegcetacoplan increased hemoglobin levels and decreased both reticulocyte count and total bilirubin in all six subjects. Improvements were observed in Functional Assessment of Chronic Illness Therapy Fatigue scores. Two subjects discontinued for reasons unrelated to pegcetacoplan. All four subjects who completed the study transitioned to pegcetacoplan monotherapy following eculizumab discontinuation and avoided transfusions. In this small study, pegcetacoplan therapy was generally well‐tolerated, and resulted in an improved hematological response by achieving broad hemolysis control, enabling eculizumab discontinuation.